Partisipasi Kaum Awam Dalam Bidang Politik Menurut Dekrit Konsili Vatikan Ii Apostolicam Actuositatem - Rikardus Jehaut (STIPAS St. Sirilus Ruteng, 2018)
Since the Second Vatican Council, the emphasis on the dignity and the role of the laity in the Church and society has been one of the important developments in ecclesiology. And given to the fact that it is proper to the laity ’s state to live both in the midst of the world and of secular transactions, the typical mark or special characteristic of the laity ’s participation in the mission of the Church is an apostolate exercised in and through direct concern with secular affairs, particularly in politics. In this regard, the decree Apostolicam Actuositatem, particularly in articles 7 and 14 has inspired the laity by stating that Catholics versed in politics, firm in the faith and Christian teaching, should not decline to enter public life.This article will examine - in the light of the teaching of the decree - how Catholic lay members can contribute to promoting the common good through their participationin politics. And in order to fully realize the mission of the laity in politics, there is need for lay formation and authentic collaboration between the clergy and the laity. It will also demonstrate how an effective transformation of the laity can be achieved through their socialization in the social teaching of the Church with regard to how they can contribute to the promotion, protection, and preservation of the common good.